2002
DOI: 10.1177/014616702237644
|View full text |Cite
|
Sign up to set email alerts
|

Consuming Images: How Television Commercials that Elicit Stereotype Threat Can Restrain Women Academically and Professionally

Abstract: Women in quantitative fields risk being personally reduced to negative stereotypes that allege a sex-based math inability. This situational predicament, termed stereotype threat, can undermine women's performance and aspirations in all quantitative domains. Gender-stereotypic television commercials were employed in three studies to elicit the female stereotype among both men and women. Study 1 revealed that only women for whom the activated stereotype was self-relevant underperformed on a subsequent math test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
414
5
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(446 citation statements)
references
References 30 publications
16
414
5
11
Order By: Relevance
“…A sizable literature has demonstrated insidious consequences for motivation and achievement when people anticipate that they might be stereotyped. For instance, compared to women who were exposed to neutral or counter-stereotypic television commercials, women who watched gender-stereotypic television commercials subsequently underperformed on a math test (Davies et al 2002) and avoided leadership roles in favor of nonthreatening subordinate roles (Davies, Spencer, and Steele 2005).…”
Section: Stereotype Threat In Consumption Settingsmentioning
confidence: 99%
“…A sizable literature has demonstrated insidious consequences for motivation and achievement when people anticipate that they might be stereotyped. For instance, compared to women who were exposed to neutral or counter-stereotypic television commercials, women who watched gender-stereotypic television commercials subsequently underperformed on a math test (Davies et al 2002) and avoided leadership roles in favor of nonthreatening subordinate roles (Davies, Spencer, and Steele 2005).…”
Section: Stereotype Threat In Consumption Settingsmentioning
confidence: 99%
“…Because both the memorize and impression groups were told they would be asked questions about the items they would be exposed to, we thought it possible that the general testing situation might have had features that triggered older adults' negative views about their performance ability. This seemed plausible because very subtle manipulations can trigger negative stereotypes (e.g., Davies, Spencer, Quinn, & Gerhardstein, 2002;Steele & Aronson, 1995). To explore this possibility, we conducted a second study to directly examine participants' cognitive and affective experiences during the testing situation.…”
Section: Studymentioning
confidence: 99%
“…Based on earlier studies (i.e., Davies, et al, 2002), the media's failure to represent women's diverse roles in real life reinforces audience members' stereotypical expectations of women. Researchers (Siu & Au,1997;Kang & Xu, 2009) have observed that media tended to portray females as sexually attractive, and, indeed, most of the participants seemed to enjoy the fact that these actresses met conventional standards of beauty.…”
Section: Chapter 5 Discussionmentioning
confidence: 99%
“…The authors thus concluded that television commercials presenting women as independent, confident, dominant, and active have positive effects on women's self-perception. Davies, et al (2002) found that women who viewed genderstereotyped television commercials tended to underperform on a math test or even avoid quantitative work. The researchers concluded that "experiencing stereotype threat repeatedly in a given domain may eventually lead from action to chronic adaption strategies" (p. 1627).…”
Section: Everdeen From the Hunger Games) Television Series Like Kingmentioning
confidence: 99%